Information ambiguity and firm value - Katrin Hussinger; Sebastian Pacher (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
A recent theoretical model by Epstein and Schneider (2008) predicts that a firm's assets will be undervalued by the market if the information surrounding these assets is ambiguous. The model further predicts that this effect is amplified if the underlying fundamentals are volatile. This paper provides an empirical test.
urn:nbn:de:bsz:180-madoc-373800
Keywords: 330